Diversity issues in the diagnosis, treatment, and research of mood disorders - Loue, Sana; Sajatovic, Martha (Oxford University Press, 2008)
1. Using Care with Culture, Jeffrey L. Longhofer, Elizabeth Song Carpenter, and Megan Nordquest. 2. Issues in the Diagnosis and Assessment of Mood Disorders in Minorities, Humberto Marin and Javier Escobar. 3. Culture-Specific Diagnoses and Their Relationship to Mood Disorders, Peter Guarnaccia and Igda Martinez Pincay. 4. The Epidemiology of Mood Disorders Among U.S. Minority Populations, Sana Loue. 6. Health Care Seeking and Access, Earnestine Willis and Sheryl E. Allen. 7. The Scientific Status of Complementary and Alternative Medicines for Mood Disorders: A Review, Declan Barry and Mark Be.